2012
DOI: 10.1186/1471-2261-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum uric acid and internal carotid resistive index in hypertensive women: a cross-sectional study

Abstract: BackgroundThe impact of serum uric acid (SUA) on arteries of hypertensive subjects remains to be fully established. This study investigated the relationship between SUA and carotid structural and hemodynamic parameters in hypertensive men and women.MethodsThree hundred and thirty eight patients (207 women and 131 men) were cross-sectionally evaluated by clinical, laboratory, hemodynamic and carotid ultrasound analysis. Common carotid diameters, circumferential wall tensions, Young’s Elastic Modulus, Stiffness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…In the present study, we found no difference in the associations between uric acid and femoral stiffness or carotid stiffness. In line with our study, Cipolli et al [29] did not identify an association between uric acid and carotid YEM or carotid compliance coefficient in 338 individuals with hypertension. In addition, an association between uric acid and carotid distensibility coefficient was not found among young adults [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found no difference in the associations between uric acid and femoral stiffness or carotid stiffness. In line with our study, Cipolli et al [29] did not identify an association between uric acid and carotid YEM or carotid compliance coefficient in 338 individuals with hypertension. In addition, an association between uric acid and carotid distensibility coefficient was not found among young adults [30].…”
Section: Discussionsupporting
confidence: 92%
“…Studies that investigated the relation between uric acid and local arterial stiffness indices are scarce [29,30]. However, assessing local carotid stiffness indices may be of importance [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Atherosclerosis Risk in Communities (ARIC) Study also found a correlation between the uric acid level and an elevated CIMT in men; however, that correlation was not independent of the use of diuretics 34) . In contrast, no association between the serum uric acid level and carotid atherosclerosis was observed in the Korean Multi-Rural Communities Cohort study or a cohort of hypertensive women 35,36) ; these study participants were restricted to specific populations of rural areas or females patients with hypertension. Hence, data for the general population are scare, especially in Chinese populations.…”
Section: Resultsmentioning
confidence: 97%
“…In the literature, we have found that Cipolli et al examined cross-sectionally 338 hypertensive patients (207 women and 131 men) and showed that internal carotid artery resistive index was independently associated with hyperuricemia in women. In their study, patients who had suffered a gout attack were not included [25]. In contrast, we estimated that gouty tophi increased the patients' likelihood of having abnormal value of CCARI twice than arterial hypertension, as hyperuricemia did not appreciably modify the odds of having abnormal value of CCARI.…”
Section: Discussionmentioning
confidence: 99%